How efficient is Peruvian technology management system? - Tavera Colonna, Jazmín (2015)
When we talk about our little technological development achieved always points to the little intended budget for this purpose, however, if this deficiency will be remedied we could not achieve the objective, as our national science , technology and innovation yet has structural flaws that determines very low meso efficiency of the system to recreate the dynamics of innovation in our country.